Bone and Cartilage Regeneration - Pham, Phuc Van (Stem Cells in Clinical Applications,, 2016)
This invaluable resource discusses clinical applications with effects and side-effects of applications of stem cells in bone and cartilage regeneration. Each chapter is contributed by a pre-eminent scientist in the field and covers such topics as skeletal regeneration by mesenchymal stem cells, clinical improvement of mesenchymal stem cell injection in injured cartilage and osteoarthritis, Good manufacturing practice (GMP), minimal critera of stem cells for clinical applications, future directions of the discussed therapies and much more. Bone & Cartilage Regeneration and the other books in the Stem Cells in Clinical Applications series will be invaluable to scientists, researchers, advanced students and clinicians working in stem cells, regenerative medicine or tissue engineering.